The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1108/tr-11-2018-0155
|View full text |Cite
|
Sign up to set email alerts
|

Loyalty motivations for religious tourism: Indonesian Muslim travelers umrah participating in umrah pilgrimage to Mecca, Saudi Arabia

Abstract: Purpose This paper aims to investigate how motivation aspects including expected organizational rewards (EOR) and enjoyment in helping others (EHO) drive umrah travelers’ participation. Furthermore, it verifies the effect of umrah travelers’ participation on loyalty and assesses the perceived value and umrah travelers’ satisfaction emerging in this relationship. Design/methodology/approach The survey uses the purposive sampling method. Data analysis uses confirmatory factor analysis and structural equation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 49 publications
4
32
0
1
Order By: Relevance
“…Umrah travelers' participation significantly impacts co-creation value This study confirms that service brand image, service employee performance and perceived willingness to customize successfully affect Umrah travelers' participation, supports H1-H3. The results in line with a previous study that reported extrinsic and intrinsic motivation can stimulate Umrah travelers' participation (Wu and Mursid, 2019). The significant effect of service brand image on Umrah travelers' participation relevant with previous study that informed brand experience value significantly affects customer cocreation attitude and behavior (Ahn et al, 2019).…”
Section: Conclusion and Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Umrah travelers' participation significantly impacts co-creation value This study confirms that service brand image, service employee performance and perceived willingness to customize successfully affect Umrah travelers' participation, supports H1-H3. The results in line with a previous study that reported extrinsic and intrinsic motivation can stimulate Umrah travelers' participation (Wu and Mursid, 2019). The significant effect of service brand image on Umrah travelers' participation relevant with previous study that informed brand experience value significantly affects customer cocreation attitude and behavior (Ahn et al, 2019).…”
Section: Conclusion and Discussionsupporting
confidence: 91%
“…The growing number of publications in religious tourism investigated the main topics include destination, demand and marketing (Heidari et al, 2018). Other scholars have investigated religious tourism such as the motivation aspects of Muslim travelers to choose the destination from Islamic compliance (Rahman et al, 2017) and the extrinsic and intrinsic factors of Umrah travelers' participation in enhancing loyalty (Wu and Mursid, 2019). Using a qualitative study, Handriana et al (2019) have explored pilgrimage tourism in Indonesia from various motivational perspectives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almuhrzi and Alsawafi (2017) discovered that attaining inner harmony, integrating and seeking opportunities to grow in spirituality, engaging with family and friends about the meaning of life and so on are the motivations for Umrah travel among Oman travellers. Furthermore, a study conducted by Wu and Mursid (2020) on Indonesian Muslim Umrah travellers to Makkah found that quality, price, emotions, social connections and physical and non-physical Islamic attributes are the values that lead to participation in Umrah. Although the results from both studies are inconsistent, they show that the participation of Umrah travellers promotes both hedonic and emotional values, and that there are significant variations between senior and young travellers, where senior travellers see the educational purposes and feelings of national identity related to sacred sites as important, while these are less motivating for young travellers (Irimias et al, 2016).…”
Section: Islamic Tourism and Pilgrimage Travelmentioning
confidence: 99%
“…According to the data Global Religious Future (2020), the number of Muslim population in Indonesia in 2020 will reach 229.62 million people or 87% of the population. Indonesia has potential in the field of organizing the Umrah and Hajj pilgrimages (Wu and Mursid, 2019). Public interest in performing Umrah worship is so high (Kumaladewi et al, 2017;Korayan and Djayaputra, 2018).…”
Section: Introductionmentioning
confidence: 99%